Distribution of pathological features and inflammatory cells in patients with giant cell myocarditis. (25th November 2020) - Liu, S; Hu, Z; Yao, Y
Abstract: Background: Giant-cell myocarditis (GCM) is a rare disease with a poor prognosis, the etiology and pathophysiology of GCM remain largely unclear. Purpose: Describe the distribution of GCM lesions, classify inflammatory cells, and explore the potential relationships of these features with clinical manifestations by examining the histopathological features of GCM in 8 patients who underwent heart transplantation. Methods: Eight patients with pathological diagnoses with GCM underwent heart transplantation at our center. Hematoxylin- eosin (H-E) and Masson's tri-chrome staining were performed on biopsies of the free walls of the right and left ventricles and interventricular septa of the original hearts to determine the characteristic distribution of cardiac lesions and the composition of infiltrating immune cells. A multiplex immunohistochemistry and multispectral imaging analysis were applied to further classify the specific types of inflammatory immune cells. Results: Inflammation found in a descending frequency gradually from the epicardium to the endocardium in the free wall of the left ventricle, but concentrated on the surface of right ventricular septum. Typical inflammatory infiltration and pathological changes were observed in the right-sided ventricular septum samples from all 8 patients. Numerous inflammatory immune cells, particularly CD4+ T cells, were detected in the lesion, which surrounded the emerging multinucleated giant cells. CD8+ T cells and a small number of regulatory T cells were scattered in the periphery. Conclusions: In GCM, cardiac lesions appear to concentrate particularly beneath the epicardium of the left ventricular free wall and the right side of the ventricular septum. These findings provide a rationale for the diagnostic use of conventional endocardial biopsy. The findings further suggest that myocardial injury is mediated by a variety of lymphocytes, especially CD4+ T cells. Funding Acknowledgement: Type of funding source: None